Emergency Department Evaluation and Management of Children With Simple Febrile Seizures. (September 2015) - Carapetian, Stephanie; Hageman, Joseph; Lyons, Evelyn; Leonard, Daniel; Janies, Kathryn; Kelley, Kent; Fuchs, Susan
Workup of simple febrile seizures (SFS) has changed as the American Academy of Pediatrics made revisions to practice guidelines. In 2011, revisions were made regarding need for lumbar puncture (LP) as part of the SFS workup. This study surveyed more than 100 emergency departments regarding workup of children with SFS and performed a medical record review of workup that was performed. The survey shows that laboratory workup is done routinely and LP is done infrequently. The majority documents a complete exam. The medical record review demonstrates documentation of the examination, frequent laboratory and infrequent LP evaluation. Consistent with the American Academy of Pediatrics' revisions, survey and record reviews demonstrate that LP testing is infrequent. Contrary to the guideline, laboratory studies are routinely performed. This study suggests there is an opportunity to improve management of SFS by directing efforts toward finding the source of the fever and away from laboratory workup.